ANALISIS INTERAKSI SOSIAL KERJASAMA PENGURUS DENGAN ANGGOTA PADA KELUARGA MAHASISWA KATOLIK (GAMASKA) FKIP UNTAN PONTIANAK - Jerri Jerri; Yohanes Bahari; Rustiyarso Rustiyarso (Universitas Tanjungpura, 2019)
AbstractThe research aimed to know the social interaction of committee organization with the members of the Catholik Students Family FKIP Untan Pontianak. The method was used descriptive. Data collection techniques was conducted with observations, interviews, and documentation. The tools of data collection was used observation guides, interview guides and documentation. The results of this study indicated that social interaction between the organization committee and members was carried out well: Mutual collaboration between organization committee and members of the committee, namely mutual assistance, help and community service, helping one of the members who carry out the Rosary at his home, community service the construction of a toilet in the Bukit Hati Kudus Hall, Darit. Bargaining cooperation of organization committee with members, namely integrative bargaining among others, giving suggestions at meetings forming the Gamaska Anniversary committee, holding meetings at the Gamaska Anniversary meeting.Coalition cooperation between the organization committee and members of the coalition is when parking activities in front of the Holy Family Church, the association of the organization committee with members in the social visit activities of the elderly nursing home Werdha Marie Joseph. Keywords: Gamaska, Social Interaction of Cooperation